The peripheral cannulas in extracorporeal life support - Strunina, Svitlana; Hozman, Jiri; Ostadal, Petr (Biomedizinische Technik. Biomedical engineering, 2019)
Femoral cannulation is a minimally invasive method which is an alternative method for central cannulation. This review focuses on the parameters and features of the available peripheral cannulas. Nowadays there exist many peripheral cannulas in a variety of sizes, configurations and lengths to meet the specific needs of the patients. Modern cannulas are strong, thin-walled and one piece reinforced constructions. Furthermore, modern cannulas are manufactured from a biocompatible material and surface coatings are applied to the cannulas to reduce the activation of the clotting. When peripheral cannulas are applied, bleeding, thrombosis and hemolysis are the most common complications.
Keywords: Extracorporeal Membrane Oxygenation; katetrizace; complications; Catheterization; surface coating; cannula material; cannula position; Humans; cannula dimensions; extracorporeal membrane oxygenation; lidé; mimotělní membránová oxygenace; kanyla; Cannula